MENCARI NAFKAH DENGAN MEMANFAATKAN BALITA OLEH PENGEMIS JALANAN DALAM PERSPEKTIF HUKUM EKONOMI SYARIAH (STUDI KASUS DIKAWASAN MASJID AGUNG PALEMBANG) - Rahmanita, Vivi Andini; Antasari, Rina; Sunaryo, Sunaryo (Program Studi Muamalah Fakultas Syariah dan Hukum, 2018)
Abstract In people's lives, poverty is a social problem because this problem affects every aspect of human life and also does not rule out possible contradictory actions against one's religious behavior. That in the community there is a phenomenon of begging among the poor. Begging is one way that is used by some people to seek sustenance and even many of them make begging as their daily work to earn money. In their activities, beggars are not all poor or homeless, they only pretend to attract the sympathy of many people by carrying or carrying babies, or even hiring children to other people to be invited to beg for people's mercy. The problems studied are about Seeking Livelihood By Utilizing Toddlers By Street Beggars In A Sharia Economic Law Perspective. This research is a field research (field research), using qualitative research methods by collecting data through observation, interviews and documentation. Data analysis using deductive method. Based on the results of the study that the law of begging in Islam in general is makruh and is a work that is not noble. But when viewed from the beggar mode that brings the toddler, then the law of begging becomes unclean, because beggars bring toddlers only to be used as a mode to get the mercy of others. Keywords: Finding a living, beggars, toddlers.